Study on Novel Radar Absorbing Grilles of Aircraft Engine Inlet Based on Metasurface Design Theory - Xufei Wang; Yongqiang Shi; Qingzhen Yang; Huimin Xiang; Jin Bai (Aerospace)
In modern warfare, the advancement of low detectable technology has made the reduction of an aircraft radar cross section (RCS) crucial for survivability, while engine inlets significantly impact the overall detectability index as major forward scattering sources. Inspired by radar absorbing structures (RASs) based on metasurface theory, as well as the spoof surface plasmon polariton (SSPP) theory, this paper proposes a comprehensive design of radar absorbing grilles (RAGs) which are installed at the inlet aperture of the aircraft intake, where RAGs allow airflow to cross through and absorb the detecting radar wave. To enhance the ability of electromagnetic wave attenuation, an indium tin oxide (ITO) film is added in the middle of the RAGs to change the impedance characteristics. This study clarifies the mechanism influencing radar wave absorption characteristics through design parameters (unit length and sheet resistance) and radar characteristic parameters (frequency, incident angle, and polarization mode). The absorption peak gradually shifts towards lower frequencies with the increase in unit length from 8 to 16 mm of the grille. The integrated average absorption first increases and then decreases with the increase in sheet resistance from 100 to <semantics>800 Ω/□</semantics> applied as ITO film in the middle of the grille. When the unit length of RAG is 12 mm and <semantics>400 Ω/□</semantics>, the sheet resistance is applied, and a 90% absorption bandwidth is achieved to 100% within the 8–18 GHz band. The 90% absorption bandwidth reaches 72.3% in the 2–18 GHz band while maintaining absorption above 40% in the 2–8 GHz band. The integrated average absorption reaches 0.887, and the 90% absorption bandwidth increases to 255.6% of the original model’s bandwidth. The results indicate that the proposed RAGs based on metasurface exhibit broadband absorption performance and high angular stability, providing technical support for further application of these grilles in aircraft engine inlets.